2014
DOI: 10.1007/s00049-014-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific responses of southern pine beetle (Dendroctonus frontalis) and its clerid predator, Thanasimus dubius, to α-pinene

Abstract: Multi-trophic interactions between pine bark beetles, their host trees, and predators are mediated in part by volatile terpenes in host tree oleoresin that can influence aggregation and/or host finding by both prey and predator species. The southern pine beetle, Dendroctonus frontalis Zimmermann, mass-attacks pine trees in response to its aggregation pheromone combined with host resin odors including a-pinene. We investigated discrimination of apinene enantiomers in olfactory responses of D. frontalis, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The prey-associated plant volatiles played a crucial role in the prey location process of D . helophoroides , as demonstrated in another coleopteran predator Thanasimus dubius for the forest pest Dendroctonus frontalis [ 29 ] . D .…”
Section: Discussionmentioning
confidence: 99%
“…The prey-associated plant volatiles played a crucial role in the prey location process of D . helophoroides , as demonstrated in another coleopteran predator Thanasimus dubius for the forest pest Dendroctonus frontalis [ 29 ] . D .…”
Section: Discussionmentioning
confidence: 99%
“…(Mirov, 1961). The (+)-enantiomer of α-pinene is a better synergist than the (À)-enantiomer, and EAG cross-adaptation studies indicated that both sexes possess at least some receptors with differing affinities for the two enantiomers (Staeben et al, 2015). The antennae also have a lower response threshold to (+) than (À)-α-pinene.…”
Section: Host Monoterpenesmentioning
confidence: 97%
“…Thanasimus dubius apparently locate D. frontalis-attacked trees primarily by responding to frontalin and host monoterpenes (Vit e and Williamson, 1970). In experimental trials the host component could be presented as either α-pinene or distilled pine resin (Billings, 1985;Billings and Cameron, 1984;Costa and Reeve, 2011;Staeben et al, 2015;Vit e and Williamson, 1970). Thanasimus dubius may sometimes be observed congregating on pines where D. frontalis brood beetles are emerging (Clarke and Menard, 2006), presumably because the emergent D. frontalis contain their aggregation pheromone (Pureswaran et al, 2007) and are apparently "leaking" it in sufficient quantities during emergence to attract this predator.…”
Section: Exploitation Of D Frontalis Pheromone By Predators and Paramentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars from different scientific backgrounds have done extensive research on infestation, spread, and outbreak patterns of SPB. Biologists (Hofstetter, Cronin, Klepzig, Moser, & Ayres, 2006;Vasanthakumar et al, 2006) have studied the individual SPB infestation behavior, while forest entomologists (Fargo, Coulson, Pulley, Pope, & Kelley, 1978;Staeben, Sullivan, Nowak, & Gandhi, 2015;Strom, Meeker, Bishir, Roberds, & Wan, 2016) have studied the SPB outbreaks at the stand scale. In addition, SPB outbreaks across tree stands and at the landscape level have been evaluated (Niemiec, Lutz, & Howarth, 2014;Nowak, Meeker, Coyle, Steiner, & Brownie, 2015).…”
Section: Introductionmentioning
confidence: 99%